Prevalence and predictors of maternal smoking prior to and during pregnancy in a regional Danish population: a cross-sectional study - Mie Gaarskjaer de Wolff; Mette Grønbæk Backhausen; Mette Langeland Iversen; Jane Marie Bendix; Ane Lilleøre Rom; Hanne Kristine Hegaard (BMC, 2019)
Abstract Background Maternal smoking is still a major public health problem posing the risk of several negative health outcomes for both the pregnant woman and her offspring. The prevalence of maternal smoking in Denmark and other high-income countries has decreased continuously since the 1980s, and a prevalence below 10% of women who continue to smoke during pregnancy has been reported in studies after 2010. Previous studies have shown that low socioeconomic status is associated with maternal smoking. Information from the Danish Birth Register about maternal smoking shows that the prevalence of women who report to smoke in pregnancy has decreased continuously with 23.3% who reported ever smoking in pregnancy in 2000, 12.9% in 2010 and 9.0% in 2017. The aim of this study was to estimate the prevalence of maternal smoking at the time of conception and at 20 weeks of gestation in a regional Danish population, to describe differences in maternal characteristics among smokers, quitters and never-smokers, and to estimate predictors of smoking at the time of conception. Methods A cross-sectional study was conducted among pregnant women receiving antenatal care at the Department of Obstetrics, Zealand University Hospital, Denmark from August 2015 to March 2016 (n = 566). The main outcome was smoking at the time of conception and at 20 weeks of gestation. The questionnaire also collected information about maternal, health-related and sociodemographic characteristics. Descriptive analysis was conducted, and multivariate logistic regression analysis was used to assess the potential associated predictors (adjusted odds ratio). Results The prevalence of self-reported smoking at the time of conception was 16% (n = 90) and 6% smoked at 20 weeks of gestation (n = 35), as 61% of smokers quit smoking during early pregnancy. Multiple logistic regression analysis showed that significant predictors for smoking at conception were the socioeconomic factors; ≤12 years of education, shift work and being unemployed. Conclusion The prevalence of self-reported maternal smoking in this regional Danish population of pregnant women is lower than seen in previous studies. However, predictors for smoking at the time of conception remain to be factors of low socioeconomic status confirming a social inequality in maternal smoking. Women at risk of smoking during pregnancy must be identified in early pregnancy or even before pregnancy and be offered interventions to help them quit smoking.